Donde no hay política: lucha, rezos y traición en Chiapas - Larsson, Martin; Cameras Myers , Mariel (El Colegio de México, 2023)
In contemporary anthropological literature, the use of the term “politics” is widespread, although reflections on its meaning are less common. This is particularly true concerning the everyday use of the term. In this article, in contrast, we focus on the use of the term “politics” among members of various organizations in Chiapas, Mexico. We argue that their ways to use the term reflect a discursive opposition between politics on the one hand, and the people, faith and morals on the other, which shows conceptualizations of politics that are not present in the anthropological literature on the topic.